The Constitutionality of the First Amendment Law No. (25) of 2021 to the Federal Supreme Court Law No. (30) of 2005 - Abdul-Kadhim, Mohammed; Jadia, Ali (Journal of Legal Sciences, 2025)
The existence of constitutional judiciary in every state, along with its composition, jurisdiction, and safeguards, is considered one of the key topics in the field of constitutional law in general, and in light of the provisions of the Constitution of the Republic of Iraq of 2005 in particular. This importance arises from the fact that this is the first time such a judiciary has been introduced in an Iraqi constitution, represented by the Federal Supreme Court. Previous Iraqi constitutions either lacked the presence of such a judiciary entirely or included it in a formal or symbolic manner without granting it the powers necessary to function effectively. In contrast, the 2005 Constitution explicitly outlined the structure, jurisdiction, and safeguards of the Federal Supreme Court, recognizing its establishment as part of the political transformation that occurred in 2003, and based on the (now repealed) Law of Administration for the State of Iraq for the Transitional Period of 2004. Given the differences in the legal framework governing the Court between that transitional law and Law No. (30) of 2005, on the one hand, and between its legal framework under the 2005 Constitution and the First Amendment Law No. (25) of 2021, on the other hand, it becomes essential to highlight the distinctions between these legal arrangements in three key aspects: the composition, the jurisdiction, and the safeguards of the Federal Supreme Court. Moreover, it is crucial to examine the constitutionality of the First Amendment to the Court’s Law. Therefore, this significant topic warrants careful study and analysis.